POEMS Syndrome: a Rare Cause of Adrenal Insufficiency in a Young Male - Prokop, J (2019)
Summary: POEMS syndrome (Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal protein and Skin changes) is a rare multisystemic disease. Clinical presentation is variable, the only mandatory criteria being polyneuropathy and monoclonal gammapathy in association with one major and one minor criterion. Primary adrenal insufficiency is rarely reported. We describe a case of a 33-year-old patient, in whom the presenting symptoms were mandibular mass, chronic sensory-motor peripheral polyneuropathy and adrenal insufficiency. The laboratory evaluation revealed thrombocytosis, severe hyperkalemia with normal renal function, normal protein electrophoresis and negative serum immunofixation for monoclonal protein. Endocrinologic laboratory work-up confirmed Addison's disease and revealed subclinical primary hypothyroidism. Thoracic abdominal CT showed hepatosplenomegaly, multiple sclerotic lesions in thoracic vertebra and ribs. The histopathologic examination of the mandibular mass was nondiagnostic. Bone marrow biopsy revealed plasma cell dyscrasia and confirmed POEMS syndrome. Axillary lymphadenopathy biopsy: Castleman's disease. Gluco-mineralocorticoid substitution and levothyroxine therapy were started with clinical improvement. Autologous hematopoietic cell transplantation (HCT) was planned, cyclophosphamide induction was started. Meanwhile the patient suffered two ischemic strokes which resulted in aphasia and hemiparesis. Cerebral angiography revealed vascular lesions compatible with vasculitis and stenosis of two cerebral arteries. The patient deceased 14 months after the diagnosis. The young age at presentation, multiplicity of manifestations and difficulties in investigation along with the absence of serum monoclonal protein made the diagnosis challenging. We report this case to highlight the need to consider POEMS syndrome in differential diagnosis of peripheral neuropathy in association with endocrine abnormalities even in young patients. Learning points: POEMS syndrome is considered a 'low tumor burden disease' and the monoclonal protein in 15% of cases is not found by immunofixation. Neuropathy is the dominant characteristic of POEMS syndrome and it is peripheral, ascending, symmetric and affecting both sensation and motor function. Endocrinopathies are a frequent feature of POEMS syndrome, but the cause is unknown. The most common endocrinopathies are hypogonadism, primary hypothyroidism and abnormalities in glucose metabolism. There is no standard therapy; however, patients with disseminated bone marrow involvement are treated with chemotherapy with or without HCT.